Fertility and Parental Labor-Force Participation : New Evidence from a Developing Country in theBalkans - Trako, Iva (World Bank, Washington, DC, 2019)
This paper examines the effect of fertility on parental labor force participation in a developing country in the Balkans, with particular attention to the intervening role of childcare provided by grandparents in extended families. To address the potential endogeneity in the fertility decision, the analysis exploits the Albanian parental preference for having sons combined with the siblings' sex-composition instrument as an exogenous source of variation. Using a repeated cross-section of parents with at least two children, the analysis finds a positive and statistically significant effect of fertility on parental labor supply for parents who are more likely to be younger, less educated, or live in extended families. The IV estimates for mothers show that they increase labor supply, especially hours worked per week and the likelihood of working off-farm. Similarly, fathers' likelihood of working off-farm and having a second occupation increase as a consequence of further childbearing. The heterogeneity analysis suggests that this positive effect might be the result of two plausible mechanisms: childcare provided by non-parental adults in extended families and greater financial costs of maintaining more children.